2019
DOI: 10.29261/pakvetj/2018.118
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Study of Mastitis in Three Different Strains of Beetal Goat in Selected Districts of Punjab, Pakistan

Abstract: Mastitis in goats, analogous to dairy cattle, is among the momentous diseases of economic value in all parts of the world. Local information of epidemiology of goat mastitis is scanty. In the present study, considering geographical distribution of Beetal goat, 172 flocks were randomly pulled out by "Survey tool box" to reduce biased sampling from perie-urban and urban areas of six districts of Punjab. By following the proportionate sampling strategy and assuming the highest population (70%) of Beetal all over … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 16 publications
0
8
0
Order By: Relevance
“…Staphylococcus aureus (S. aureus) infection is one of the most common nosocomial and community-acquired infections in humans and animals [1,2]. Almost 30% of the human population is asymptomatically colonized with commensal S. aureus [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Staphylococcus aureus (S. aureus) infection is one of the most common nosocomial and community-acquired infections in humans and animals [1,2]. Almost 30% of the human population is asymptomatically colonized with commensal S. aureus [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Methicillin resistance is generally caused by mecA gene that encodes polypeptide PBP2a protein [8]. Within the past few decades, there has been an alarming increase in prevalence of antibiotic resistance in pathogens as well as in commensals [2]. Glycopeptides, especially vancomycin, are generally used against methicillin-resistant Staphylococcus aureus (MRSA) since the last few decades of 20th century [9].…”
Section: Introductionmentioning
confidence: 99%
“…Oppositely to our findings, the prevalence of SCM is 76.7% and 15-79%, respectively, in goats, when screened with CMT [ 48 , 49 ]. Similarly, prevalence SCM is 32.4%, 39.2%, 38%, 40.2%, 47%, 14.3%, 38.8%, 19.9%, and 35.5%, respectively, by Saleem [ 4 ], Ali et al . [ 21 ], Altaf et al .…”
Section: Resultsmentioning
confidence: 98%
“…[ 21 ]. It was reported that Staphylococcus is more dominant in Pakistan in terms of SCM infections [ 4 ]. Similarly, it was reported that S. aureus was predominant in milk samples [ 21 ], while Manser (2000) recorded the incidence of catalase-negative Staphylococcus and catalase-positive staphylococci at 80% and 16%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation